Radiofrequency ablation combined with transarterial chemoembolization for unresectable primary liver cancer - Wang, Yue-hua; Liu, Jia-feng; Li, Fei; Li, Ang; Liu, Qiang; Liu, Dong-bin; Liu, Dian-gang; Wang, Ya-jun (Chinese medical journal, 2009)
Background Radiofrequency ablation （RFA） followed by transarterial chemoembolization （TACE） for unresectable primary liver cancer （PLC） has not been widely discussed. In this study, the outcome of the combination of RFA with TACE was retrospectively evaluated. Methods From May 2003 to March 2008, 127 consecutive PLC patients with a median age of 56.4＋8.8 years underwent RFA plus TACE. All patients were deemed to have unresectable PLC based on their tumor characteristics. The maximal diameter of the tumor was between 1.5 cm and 10.0 cm. Twenty-six cases with small （〈3.0 cm）, 33 with medium （3.1-5.0 cm）, and 68 with large （〉5.0 cm） tumors were included in this study. RFA was performed using a RITA Medical Systems expandable electrode device, which was followed by first-time TACE administration one to two months later. Results Technical success of RFA was achieved in all 127 patients with no severe treatment-related complications. RFA was performed percutaneously in 16 （13.5%） cases, by laparoscopic approach in 19 （15.7%）, and through laparotomy in the remaining 92 （72.4%）. RFA response was classified as complete ablation in 48 cases, nearly complete ablation in 28, and partial ablation in 51. The total 1-, 2-, and 3-year survival rates after RFA were 83.1%, 55.7%, and 43.7%, respectively. The survival rates at 3 years were 78.6%, 28.1%, and 0 for complete ablation, nearly complete ablation, or partial ablation groups, respectively. Three-year disease-free survival rates for the complete ablation and nearly complete ablation groups were 50.3% and 21.3%, respectively. RFA response and liver function were significant variables influencing survival time as analyzed using the Cox regression model. Conclusion RFA could be the first-line exterminate treatment for unresectable PLC, and TACE following RFA may assist in eradicatinq the peripheral viable tissue and micro-metastasis.